2021
DOI: 10.1016/j.jamcollsurg.2021.05.003
|View full text |Cite
|
Sign up to set email alerts
|

State-Level Examination of Clinical Outcomes and Costs for Robotic and Laparoscopic Approach to Diaphragmatic Hernia Repair

Abstract: BACKGROUND: Published studies evaluating the effect of robotic assistance on clinical outcomes and costs of care in diaphragmatic hernia repair (DHR) have been limited. STUDY DESIGN: The Healthcare Cost and Utilization Project State Inpatient and State Ambulatory Surgery and Services Databases for Florida were queried to identify patients undergoing transabdominal DHR between 2011 and 2018 and associated inpatient and outpatient encounters within 12 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Only O'Connor et [3][4][5]7,8,22]. (B) Meta-analysis of length of stay [4,5,[7][8][9][10]22,27,28]. (C) Meta-analysis of mean operation time [4,5,7,9,10,27].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only O'Connor et [3][4][5]7,8,22]. (B) Meta-analysis of length of stay [4,5,[7][8][9][10]22,27,28]. (C) Meta-analysis of mean operation time [4,5,7,9,10,27].…”
Section: Resultsmentioning
confidence: 99%
“…Lekarczyk et al [ 27 ] found similar hospital profits for the robotic group despite higher supply costs and charges. However, Kulshrestha et al [ 28 ], in a study with more participants, reported that both open and robotic-assisted procedures had significantly higher median index hospitalization costs compared to laparoscopic ones. The most common reasons that increased the cost were upper endoscopy and reoperation, followed by emergent priority, increased comorbidity index, and LOS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it still proves to be disadvantageous when it comes to costs. This was displayed by Kulshrestha’s et al , in which the authors reported robotic surgery having comparable clinical outcomes, but a higher index cost when compared to laparoscopic surgery ( 78 ). In another study, Kulshrestha et al described the existence of a 2-fold variation between diaphragmatic hernia repair costs between various hospitals ( 79 ).…”
Section: Robotic Giant Paraesophageal Hernia (Peh) Repairmentioning
confidence: 95%